Handling the challenge of antimicrobial resistant superbugs in the clinical setting: nursing staff as a pivotal player - Marco Coppi; Ilaria Baccani; Claudia Niccolai; Alberto Antonelli; Tommaso Giani; Gian Maria Rossolini (Infermieristica Journal, 2022)
Bacterial resistance to antibiotics (antimicrobial resistance, AMR) is spreading globally among major Gram-positive and Gram-negative bacterial pathogens (including staphylococci, enterococci, Enterobacterales, Pseudomonas aeruginosa and Bacterial resistance to antibiotics (antimicrobial resistance, AMR) is rapidly spreading globally among major Gram-positive and Gram-negative bacterial pathogens (including staphylococci, enterococci, Enterobacterales, Pseudomonas aeruginosa, and Acinetobacter baumannii); this phenomenon has a remarkable impact on morbidity, mortality and healthcare-associated costs. Evolution and dissemination of AMR can be counteracted with a combined strategy based on i) antimicrobial stewardship programs aimed at a prudent and appropriate use of antibiotics to improve clinical outcomes and reduce the selective pressure for resistance; and ii) infection prevention and control (IPC) practices, to limit the spread of resistant pathogens within the healthcare settings. In this scenario, the nursing staff plays a pivotal role, since these figures are involved in the enforcement and supervision of IPC bundles (e.g., contact precautions, hand, and environmental hygiene, active surveillance, patient isolation, or cohorting), which are essential to limit the spread of resistant pathogens among different patients.